Philosophical education asexpe rience and possibility (2012)
This article aims at presenting in a conceptual way the importance of developing the philosophical attitude in students and teachers, as a possibility, a condition and an experience for nowadays education. Methodologically speaking, it describes and clarifies the statements and practices concerning the philosophical attitude and its interaction with the educational and pedagogical processes. Thematically speaking, this paper is organized in different sections dealing with the definition of philosophy as a creation of concepts, the answer for the question: ‘what is the philosophical attitude?’, and the relationship between education and philosophy. Finally, a methodological way to develop this attitude in the classroom through the questioning is proposed.This proposal attempts at reflecting on the need for the philosophical exercise in contemporary school as well as putting forward the philosophical attitude as a didactical tool to philosophize in the classroom.